PKM Usaha Mikro Camilan di Kecamatan Donomulyo Kabupaten Malang - Dyah Aruning Puspita; Marli Marli (Jurnal ABM Mengabdi, 2018)
Donomulyo Subdistrict is one of the Districts in Malang Regency, it is more convenient to be close to quite famous tourism objects, namely Ngiyep Beach, Bajul Mati beach and Ngebros beach. This area has a population of almost 50%, which is poor and most of the people's livelihoods are planted on land that relies on rain. The partners in community service are 2 (two) micro-snack entrepreneurs whose production is processing bananas into banana chips, cassava chips, banana sake chips and processing various types of crackers and then spice them up and sell them in plastic packaging ready to be eaten. The production process of each partner still uses very simple equipment so that the increasing market opportunity still cannot be utilized maximally by micro entrepreneurs. The marketing area of ​​partner products is in schools and food stalls and in vegetable vendors who are traveling around the community every day, in shops in Malang City, and there are even people who sell online. It is hoped that the Community Entrepreneurship program will have an impact on the growing development of these micro-enterprises which can create greater employment opportunities so that they can absorb labor in the village, which the average population lives below the poverty line.